Pembangan dan Validasi Metode Kromatografi Lapis TipisDensitometri untuk Analisis Pewarna Merah Sintentik pada Beberapa Merek Saus Sambal Sachet - Fithriani Armin; Bita Revira; Adek Zamrud Adnan (Jurnal Sains Farmasi & Klinis, 2015)
Chili sauce sachet A, B and C containing synthetic red coloring agent  were taken from three fast food premises in Padang. Synthetic red coloring agent  were a food additives used by food manufacturers to enhance color of food products. The use of food coloring agent in Indonesia were regulated   in The Rule of Head of the Supervisory Food Board of the Republic of Indonesia Number 37 Year 2013 about the Limit Use of Food Coloring Agent. Thin-layer chromatography (TLC) -densitometry was  a precision method for the analysis of food additives. Development and validation of TLC method for chromatographic separation used GF254 silica plate eluted with a mixture of ethanol: butanol: distilled water (4: 5: 5) and spots were detected visually. A red spots on the sample B was identified as Ponceau 4R with Rf value of 0.76. It was then followed by quantitative analysis using densitometry. The linearity of the method  was found in the range of 2-10μg/ml with a correlation coefficient of 0.994. Precision intra-day and inter-day relative standard deviation was shown from 1.11% and 2.69% respectively. Accuracy of the method was shown on the percentage of recovery of the 3 different concentrations of solution which gave the average percentage of 108.17%. Limit of detection and limit quantitation was 0.8306μg/ml and 2.7687μg/ml.  The concentration of Ponceau 4R in the sample B was 11.9520mg/kg of material. This value was not exceeded the  maximum concentration of food coloring agent as stated in the rule which should not be above 70mg/kg of material.